2016
DOI: 10.18805/ijare.v0iof.8439
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antagonistic effect of isolated Trichoderma sp. against pathogens under Clusterbean (Cyamopsis tetragonoloba L.)

Abstract: A green house experiment was conducted at Department of Plant Pathology, College of Agriculture, Bikaner, to characterize the eight isolates of Trichoderma sp. ( TH-8, TH-SOG, TH-HMG, TH-BKN, TH-SIK, TH-DUP, TH-JOB and TH-JAI) were collected from different locations of clusterbean (Cyamopsis tetragonoloba L.) fields in western Rajasthan and tested for their antagonistic property against soil borne plant pathogens. It was further studied for morphological and physiological characteristics such as color of mycel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
6
4
0
Order By: Relevance
“…Similarly, based on colony shape, 4 groups were formed namely Group I, II, III and IV accommodating 16.67, 16.67, 25 and 41.66 per cent isolates, respectively. Present results were in close agreement with the observations of different workers around the world [30,31,32] who also found that the colonies of various Trichoderma isolates were at cottony, uffy or raised and at granular in texture having regular or irregular margins on PDA medium. Sharma and Singh [33] also reported that the majority of Trichoderma isolates showed different colony colour like dark green (12 isolates), whitish green (9 isolates), light green (6 isolates) and rest of the isolates (3) had yellowish green colonies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, based on colony shape, 4 groups were formed namely Group I, II, III and IV accommodating 16.67, 16.67, 25 and 41.66 per cent isolates, respectively. Present results were in close agreement with the observations of different workers around the world [30,31,32] who also found that the colonies of various Trichoderma isolates were at cottony, uffy or raised and at granular in texture having regular or irregular margins on PDA medium. Sharma and Singh [33] also reported that the majority of Trichoderma isolates showed different colony colour like dark green (12 isolates), whitish green (9 isolates), light green (6 isolates) and rest of the isolates (3) had yellowish green colonies.…”
Section: Discussionsupporting
confidence: 93%
“…The highest mycelial dry weight was recorded in PR2 isolate and the least in PTi3 isolate. A signi cant variation in terms of mycelial dry weight of different isolates of Trichoderma was also reported by different workers[32,49,50,51,52].…”
supporting
confidence: 56%
“…Further increase in dry weight observed with the application of zinc (20 kg/ha) might be due to Zinc application creating a balanced nutritional environment which enhanced metabolic activities and photosynthetic rate, resulting in improvement and ultimately accumulation of plant dry matter. Similar types of results were reported by Meena et al [11].…”
Section: Plant Dry Weight (G)supporting
confidence: 92%
“…The most commonly used biopesticides include Bacillus thuringiensis (Bt), Baculo viruses, Trichoderma, Azadirachta indica. PIPs, for example, Bacillus thuringiensis is the most globally popular, which is being used against moth larvae on plants, and the strains are made specifically for the larvae of mosquitoes and flies [121]. Important among microbial biopesticides are: (1) the Baculo viruses to target specific viruses which exterminates the disease-causing to lepidopterous insects of cotton, rice, and vegetables [122], 2Trichoderma and Trichoderma-based products being effective against soil-borne diseases (i.e., root rot) and control of rots and wilts in dryland crops such as black gram (Vigna mungo), groundnut (Arachis hypogaea), chickpea (Cicer arietinum) and green gram (Vigna radiate) [120] and (3) the entomopathogenic nematodes (EPNs) of the genera Heterorhabditis sp.…”
Section: Biopesticidesmentioning
confidence: 99%